Combination of Auranofin and ICG-001 Suppress the Proliferation and Metastasis of Colon Cancer - Lin, Zhaoyan; Li, Qingqing; Zhao, Ying; Lin, Zixiang; Cheng, Nan; Zhang, Di; Liu, Gang; Lin, Jiahao; Zhang, Hong; Lin, Degui (Frontiers in Oncology, 2021)
Colon cancer is one of the deadliest tumors in the world, with high metastasis rate and mortality, effective drugs for its treatment are still in need. Auranofin (AF) is a gold complex that has been attested by FDA for treating human rheumatism, and researchers have found that AF acts as a great anti-tumor drug in recent years. ICG-001 is a small molecule inhibitor of Wnt/β-catenin pathway. In the present study, we aimed to explore the synergistic anti-tumor effects and the underlying mechanisms of AF and ICG-001 combination therapy on human colon cancer. The results showed that AF and ICG-001 synergistically depressed the growth and invasion of human colon cancer cells by inhibiting the phosphorylation of Signal Transducer and Activator of Transcription 3 (STAT3) and its downstream mediator B-cell lymphoma-2-like 1 (Bcl-xL) and inducing caspase-3-dependet apoptosis. Moreover, AF combined with ICG-001 synergistically inhibited the growth of colon cancer in subcutaneous xenograft mice models and restrained metastasis in lung metastasis mice models. In conclusion, our results demonstrated that combination of AF and ICG-001 suppressed the proliferation and metastasis of colon cancer by inhibiting STAT3 phosphorylation. Therefore, this combination therapy may possess potential therapeutic properties for human colon cancer.